Chemotherapy following immune checkpoint inhibitors in patients with locally advanced or metastatic urothelial carcinoma. (November 2022) - Meynard, Lucie; Dinart, Derek; Delaunay, Blandine; Fléchon, Aude; Saldana, Carolina; Lefort, Félix; Gravis, Gwenaëlle; Thiery-Vuillemin, Antoine; Cancel, Mathilde; Coquan, Elodie; Ladoire, Sylvain; Maillet, Denis; et al.
Abstract: Background: Recent studies suggest improvements in response to salvage chemotherapy (CT) after immune checkpoint inhibitors (ICIs) in several types of cancer. Our objective was to assess the efficacy of chemotherapy re-challenge after ICI, compared with second-line chemotherapy without previous ICI in patients with locally advanced or metastatic urothelial carcinoma (la/mUC). Methods: In this multicentre retrospective study, we included all patients with la/mUC initiating second or third-line chemotherapy from January 2015 to June 2020. We compared patients treated with second-line chemotherapy without previous ICI (CT2) and patients treated with third-line chemotherapy after ICI (CT3). The primary end-point was objective response rate (ORR) in CT3 compared with CT2. Secondary end-points included progression-free survival (PFS) and toxicities. Results: Overall, 553 patients were included. ORRs were 31.0% (95% CI, 26.5 to 35.5) and 29.2% (95% CI, 21.9 to 36.6), respectively, in CT2 and CT3, with no statistically significant differences ( P  = 0.62). In subgroup analyses, no differences in ORR were observed by Bellmunt risk group, type of chemotherapy (platinum or taxanes), duration of response to first-platinum-based chemotherapy (< or ≥ 12 months) or FGFR -status. Median PFS was 4.6 months (95% CI, 3.9 to 5.1) and 4.9 months (95% CI, 4.1 to 5.5) in CT2 and CT3, respectively, and grade 3–4 hematologic toxicity occurred in 35.0% and 22.4% of patients. Conclusion: This large multicentre retrospective study provides clinically relevant real-world data. Chemotherapy re-challenge after ICI in la/mUC achieves ORR and PFS comparable with those obtained in CT2 with an acceptable safety profile. These updated results offer more promising outcomes than historically reported with second-line chemotherapy data. Highlights: Largest retrospective study on the efficacy of CT re-challenge after ICIs in la/mUC. Third-line CT after ICIs was not associated with higher ORR compared with second-line CT. Patients derived comparable benefit of CT in both groups in terms of ORR and PFS. Chemotherapy remains a good choice as third-line therapy after ICI in la/mUC.